Enhancement of laser ablation via interacting spatial double-pulse effect - Zhou Rui (Institue of Optics and Electronics, Chinese Academy of Sciences, 2018)
A novel spatial double-pulse laser ablation scheme is investigated to enhance the processing quality and efficiency for nanosecond laser ablation of silicon substrate. During the double-pulse laser ablation, two splitted laser beams simultaneously irradiate on silicon surface at a tunable gap. The ablation quality and efficiency are evaluated by both scanning electron microscope and laser scanning confocal microscope. As tuning the gap distance, the ablation can be significantly enhanced if the spatial interaction between the two splitted laser pulses is optimized. The underlying physical mechanism for the interacting spatial double-pulse enhancement effect is attributed to the redistribution of the integrated energy field, corresponding to the temperature field. This new method has great potential applications in laser micromachining of functional devices at higher processing quality and faster speed.